Landfall - Alvarez, Jennifer Lynn (Alvarez, Jennifer Lynn. Guardian Herd, 2016)
It has been many moons since Star received his starfire power, and now he will face his toughest challenge yet. Star is gravely injured, and Nightwing the Destroyer vows to make a pact with whoever brings him the black yearling--dead or alive. As Nightwing amasses an army to destroy him and all of Anok, Star must act fast. But as the threat of war looms, Star wonders if the current peace among the united pegasi is strong enough to survive